Risk Factors Affecting Diabetes Mellitus In Primary Health Care In Bekasi City 2022 - Anisa Prameswari; Alibbirwin Alibbirwin; Trimawartinah Trimawartinah (JUKEJ : Jurnal Kesehatan Jompa, 2023)
Diabetes Mellitus (DM) is a disease caused by metabolic disorders in the pancreas. It is characterized by increased blood sugar (hyperglycemia) caused by a decrease in the amount of insulin in the pancreas (ADA, 2012). Conditions at the Village Health Center related to Diabetes Mellitus cases are always checked every month on a regular basis, starting from checking sugar to administering medicine if the patient needs it. If a patient is found to have complications during treatment, the health center will immediately refer him to the hospital for further treatment. This study aims to determine the factors that influence the incidence of diabetes mellitus in the working area of the Pejuang Village Health Center, Medan Satria District, Bekasi City, in 2022. This study is a quantitative study with a case-control design. This study has a population of 196 respondents, which are divided into 98 case respondents and 98 control respondents. Sampling in this study used a purposive sampling technique where samples were taken based on predetermined criteria. Data collection used secondary data using registration based on the national database for non-communicable diseases called Sistem Informasi Penyakit Tidak Menular (SIPTM) 2021 data. The analysis used was univariate analysis using frequency distributions and bivariate analysis using the Chi-Square test. The results of the bivariate analysis showed that there was a relationship between age, gender, fat consumption, physical activity, and family history of DM and diabetes mellitus (P < 0,05), while the variables of education, occupation, fruit and vegetable consumption did not have a relationship with diabetes mellitus (P > 0,05).